2011
DOI: 10.5380/avs.v16i2.17971
|View full text |Cite
|
Sign up to set email alerts
|

CONTAMINAÇÃO MICROBIOLÓGICA DURANTE AS ETAPAS DE PROCESSAMENTO DE FILÉ DE TILÁPIA (<i>Oreochromis niloticus</i>)

Abstract: O objetivo foi avaliar a contaminação microbiana do filé de tilápia (Oreochromis niloticus) e da água utilizada em diferentes etapas do beneficiamento desse pescado em uma indústria localizada na região metropolitana de Curitiba – PR. As amostras foram coletadas com quatro repetições e em cinco etapas do processamento do filé. Sendo duas etapas escolhidas para a coleta de amostras de água e três etapas para a coleta de filé. Os filés foram submetidos à contagem de aeróbios psicrotróficos, contagem de coliforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…and Staphylococcus coagulase (Simões et al, 2007), and higher levels were reported for viable aerobic psychrotrophic microorganisms, Escherichiacoli and Salmonella sp. (Bartolomeu et al, 2011).…”
Section: Microbiological Evaluation Of Fillets and Msmmentioning
confidence: 99%
“…and Staphylococcus coagulase (Simões et al, 2007), and higher levels were reported for viable aerobic psychrotrophic microorganisms, Escherichiacoli and Salmonella sp. (Bartolomeu et al, 2011).…”
Section: Microbiological Evaluation Of Fillets and Msmmentioning
confidence: 99%
“…Fish caught in clean waters are generally exempt from this type of bacteria. Their presence is due to the contact with infected fish, poorly cleaned surfaces and cross contamination [46,47]. In the present work, the presence of Salmonella ssp.…”
Section: Resultsmentioning
confidence: 72%
“…Oreochromis niloticus tilapias is one of the most produced fish species in freshwater aquacultures due to the high international demand (FAO, ). Due to the relevance of Brazil in tilapia production, several studies evaluated the presence of thermotolerant coliforms and E. coli in tilapia fillets and cultivation water (Bartolomeu, Dallabona, Macedo, & Kirschnik, ; Boari et al, ; Carbonera, Cappelletti, & Espírito Santo, ; Junior, Assunção, Baldin, & Amaral, ). However, none of them described factors that allow E. coli persist in tilapia‐processing facilities, which represent a more relevant information to optimize properly the manufacturing and sanitizing procedures and, thus, increase the safety of tilapia products.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hygienic conditions of Factory B were also affected by the poor quality of water. Bartolomeu et al () also reported that water polluted with coliforms contaminated tilapia fillets, but they underestimated other possible contamination sources. It is known that thermal treatments can considerably decreased the concentration of coliforms present in tilapia fillets (Emire & Gebremariam, ; Rajkowski, ).…”
Section: Discussionmentioning
confidence: 99%